Peranan Workplace Well-Being Terhadap Turnover Intention Dengan Work Engagement Sebagai Mediator Pada Karyawan Generasi Milenial (GEMA EKONOMI, 2023)
This research is motivated by the high level of job demands on PT X employees, affecting workplace well-being. There are several factors that have major influence on workplace well-being. However, this can be overcome with the job resources provided by the company. This study aims to see the role of job demands on workplace well-being with job resources as a moderator for PT X employees. The population in this study were all PT X employees and the sample used was 181 people. This study uses two measurements named The Job Demands-Resources Questionnaire by (Bakker, 2014) and The Workplace Well-being Questionnaire by (Parker & Hyett, 2011). The sampling technique used is convenience sampling. The data were processed using Moderated Regression Analysis (MRA) in the IBM SPSS version 20 program. The results showed that there was a positive role of job demands on workplace well-being for PT X employees with F = 56.101 and p = 0.000 <0.05. From the results of multiple linear regression analysis, the coefficient value RÃ‚Â² = 0.387 is obtained, the role of job demands on workplace well-being is 38.7%, while the remaining 61.3% is influenced by other factors. Other results show that job resources does not moderate the two variables in this study because the results obtained are p = 0.127 > 0.05